PENGARUH KOMPENSASI TERHADAP KINERJA MENGAJAR GURU (Jurnal Tata Kelola Pendidikan, 2019)
This study entitled the effect of compensation on teacher teaching performance at SMPK 1BPK Penabur Bandung using descriptive methods through a quantitative approach. Thedata model analysis used was literature study analysis and interviews. This study has 40respondents. The results of the compensation calculation show that the WMS calculationhas an average total indicator score of 2.58 or sufficient. Meanwhile, the Teacher TeachingPerformance based on the WMS calculation has an average total indicator score of 3.11or high. Researchers suggest that stakeholders can increase compensation to improveTeacher Teaching Performance.
Keywords: Compensation; Teaching Performance; Teacher Teaching Performance